Identification of Microplastics in the Hepatopancreas of Green Mussels (Perna viridis) in Gunung Jati Waters, Cirebon, West Java - Masode, Nelly Oktaviani; Ismail, M. Rudyansyah; Lewaru, M. Wahyudin; Agung, M. Untung Kurnia (Dinasti Research, 2026)
Microplastics are pollutants commonly found in aquatic environments and have the potential to accumulate in marine organisms, particularly filter-feeding organisms such as the green mussel (Perna viridis). This study aims to analyze the abundance, characteristics, and types of microplastic polymers using a microscope and FTIR (Fourier transform infrared) spectroscopy at two stations in the waters of Gunung Jati, Cirebon, and their accumulation in the hepatopancreas of green mussels. The results showed that the abundance of microplastics in the waters of Station 1 was 0.425 particles/L, higher than that of Station 2 at 0.325 particles/L. In the hepatopancreas of green mussels, the abundance of microplastics was higher in small mussels compared to large ones. At Station 1, the microplastic abundance in small mussels reached 5.80 ± 0.72 particles/g, while in large mussels it was 1.22 ± 0.88 particles/g. A similar pattern was also found at Station 2 with values of 4.78 ± 2.15 and 0.58 ± 0.41 particles/g, respectively. Microplastics in the water and the hepatopancreas of green mussels were dominated by fiber types with a percentage of 95–100%, and the color variation was dominated by black. The identified microplastic polymers include polyester, polyvinyl acetate, nylon, spandex, and polyethylene, as well as natural polymers such as cellulose. This research demonstrates that green mussels have the potential to serve as bioindicators of pollution in aquatic environments and provides a foundation for further research on ecological impacts and marine environmental health. Therefore, there is a need to improve plastic waste management in the Gunung Jati coastal area, as well as to educate the public on how to reduce the use of plastic waste and improve its management.